Increased oxidative stress during exercise predicts poor prognosis in patients with acute decompensated heart failure. (29th July 2021) - Shibata, Atsushi; Izumiya, Yasuhiro; Yamaguchi, Yumi; Kitada, Ryoko; Iwata, Shinichi; Ehara, Shoichi; Izumi, Yasukatsu; Hanatani, Akihisa; Yoshiyama, Minoru
Abstract: Aims: Oxidative stress plays an important role in the development and progression of heart failure (HF). Although exercise and oxidative stress are closely related, the effect of acute exercise on reactive oxygen species production and the fluctuation on prognosis are unclear. Methods and results: We enrolled 94 patients who were hospitalized for worsening HF (mean age 68.0 ± 14.5 years old, 63.8% male). The changes in diacron‐reactive oxygen metabolites (d‐ROM) values, a marker of oxidative stress, before and after a cardiopulmonary exercise test were considered as Δd‐ROM. The mean follow‐up period was 24 ± 13 months, during which 15 patients had all‐cause death or left ventricular assist system implantation. Kaplan–Meier analysis demonstrated that all‐cause death or left ventricular assist system implantation was significantly higher in the Δd‐ROM‐positive group than in the Δd‐ROM‐negative group (log‐rank P  = 0.047). Elevated Δd‐ROM levels were associated with increased mortality risk. Multivariate analysis adjusted for body mass index and peak oxygen uptake revealed that Δd‐ROM was an independent prognostic factor of adverse events (Tertile 3 vs. 1; hazard ratio: 4.57; 95% confidence interval: 1.21–29.77; P  = 0.022). Conclusions: Patients with HF who underwent a cardiopulmonary exercise test and had an increased oxidative stress marker level had a poor prognosis. The appropriate exercise intensity could be determined by evaluating the changes in oxidative stress status in response to acute exercise in patients with HF.